Immune response to progesterone involved in Cu2+-mediated polyanion-protein complex - Antigen specificity and affinity of hybridoma clones - (:unkn) unknown (ELSEVIER SCIENCE BV, 1996)
The immunogenic properties of water soluble (PAA-Cu2+-BSA) and colloidal (PAA-Cu2+-BSA.P) polycomplexes were investigated, and the specificity of antibodies produced was analyzed. Polycomplexes containing progesterone appeared to possess a high steroid-specific immunogenic activity. A comparative study of immunogenic properties of polycomplexes versus BSA.P + incomplete Freund's adjuvant (IFA) mixtures revealed differences in regards to the specificity of antibody production. In contrast to the IFA system, polycomplexes were able to generate P- as well as BSA-specific antibodies. Such a response is determined, possibly, by increases in the immunogenicity of weak antigenic determinants on the surface of protein globules and/or by the representation of 'dormant' determinants existing in the inner site upon complex formation with polyelectrolytes. Finally, using a short immunization procedure based on use of PAA-Cu2+-BSA polycomplexes, we produced seven monoclonal antibodies against progesterone included in polyelectrolyte complexes with affinities K-d ranging between 1.3 x 10(-7) and 9 x 10(-8) M.
Keywords: progesterone; polyelectrolyte complexes; Cu2+-induced complexation; immunogenicity; adjuvant; affinity; specificity; MONOCLONAL-ANTIBODIES